1894 Iowa Acts 70 - (:unkn) unknown (My University, 1894)
An Act to Restrain Hunters from Trespassing Upon Cultivated or Enclosed Lands Without Permission and Providing Penalties Therefor, ch. 64, § 1: Prohibited hunting with a gun or dog on the lands of another without obtaining the owner's permission
Keywords: HUNTING REGULATION